Emergence of racial/ethnic and socioeconomic differences in objectively measured sleep–wake patterns in early infancy: results of the Rise & SHINE study. Issue 3 (15th October 2020) - Yu, Xinting; Quante, Mirja; Rueschman, Michael; Ash, Tayla; Kaplan, Emily R; Guo, Na; Horan, Christine M; Haneuse, Sebastien; Davison, Kirsten; Taveras, Elsie M; Redline, Susan
Abstract: Study Objectives: To characterize objectively assessed sleep–wake patterns in infants at approximately 1 month and 6 months and examine the differences among infants with different racial/ethnic backgrounds and household socioeconomic status (SES). Methods: Full-term healthy singletons wore an ankle-placed actigraph at approximately 1 month and 6 months and parents completed sleep diaries. Associations of racial/ethnic and socioeconomic indices with sleep outcomes were examined using multivariable analyses. Covariates included sex, birth weight for gestational age z -score, age at assessment, maternal education, household income, bed-sharing, and breastfeeding. Results: The sample included 306 infants, of whom 51% were female, 42.5% non-Hispanic white, 32.7% Hispanic, 17.3% Asian, and 7.5% black. Between 1 month and 6 months, night sleep duration increased by 65.7 minutes (95% CI: 55.4, 76.0), night awakenings decreased by 2.2 episodes (2.0, 2.4), and daytime sleep duration decreased by 73.3 minutes (66.4, 80.2). Compared to change in night sleep duration over this development period for white infants (82.3 minutes [66.5, 98.0]), night sleep increased less for Hispanic (48.9 minutes [30.8, 66.9]) and black infants (31.6 minutes [−5.9, 69.1]). Night sleep duration also increased less for infants with lower maternal education and household income. Asian infants had more frequent night awakenings. Adjustment for maternal education and household income attenuated all observed day and night sleep duration differences other than in Asians, where persistently reduced nighttime sleep at 6 months was observed. Conclusions: Racial/ethnic differences in sleep emerge in early infancy. Night and 24-hour sleep durations increase less in Hispanic and black infants compared to white infants, with differences largely explained by SES.